(3CSS GdHMK GdYdej (B:s (3GdcJGH GdChd (B/s - (3SdGWfjI, HdbGSes; (3MSGf(B,(3GdLjdGdjs ((3GdLRGFQ (B:s (3OjhGf GdeWHhYGJ GdLGeYjI ,s, 2009)
(3CQOfG Gf fhUd gPg GdeGOI Edi GdWdGH eTQhMI eaUdI hGajI h cGajI MjK jLO ajgG WGdH GdYde eHJZGg (B,(3h jLO ajgG GdbGQF GdYGOj eG jdHj WehMg GdYdej(B, (3h jLYdg jSJajO ef GdNWhGJ GdYdejI GdeTQhMI aj GdcJGH HMjK ef NdGd GdJYeb aj GdbQGAI h JJHY GdeQGMd GdYdejI aj cjajI GdEbJHGS h GdJgejT jSJWjY Gf jUd Gdi GfLGR HMK Gh OQGSI Mhd Gj ehVhY jNJGQg Hcd SghdI hgPG eGjhaQg gPG GdcJGH ef eYdheGJ h HjGfGJ JajO LejY WdGH GdYde aFGJge ChJNUUGJge(B.s
Keywords: (3GdHMK GdYdejs; (3efgLjI GdHMKs